Association between serum Klotho and all-cause mortality in postmenopausal women: a prospective population-based cohort analysis from NHANES 2007–2016 - Bo Zhang; Ye Zhang; Tao Wang; Xing Gao (Gynecological Endocrinology)
This study investigated the association between serum Klotho levels and all-cause mortality in postmenopausal women. Utilizing data from 3,448 postmenopausal women in the US National Health and Nutrition Examination Survey (NHANES) from 2007 to 2016, multivariable-adjusted weighted Cox proportional hazards models were employed. Over a median follow-up of 106 months, 449 deaths occurred. Compared to the second tertile (T 2, 707.3-936.5 pg/mL), the adjusted HRs for all-cause mortality were 1.44 (95% CI: 1.11-1.86, p=0.005) for the first tertile (T 1, <707.3 pg/mL) and 1.31 (95% CI: 0.94-1.83, p=0.112) for the third tertile (T 3, ≥936.5 pg/mL). The restricted cubic spline model revealed an L-shaped association between serum Klotho levels and all-cause mortality, with an inflection point at an ln-transformed Klotho level of 6.638 pg/mL. Our findings suggest an L-shaped relationship between ln-transformed serum Klotho levels and all-cause mortality in postmenopausal women. Further research is needed to validate these results and elucidate the underlying mechanisms. .